The Influence of Fraud Triangle on Financial Distress with Good Corporate Governance as Moderating Variable - Sekawulan, Wening; Umar, Haryono (Economics and Business Faculty UNUSIA, 2021)
This study aims to obtain empirical evidence of the effect of triangle fraudon financial distress with good corporate governance as a moderating variable.The research sample is a manufacturing company that is listed on the IndonesiaStock Exchange and publishes audited financial statements and annual reports forthe 2015-2017 research period. Sampling is done using purposive sampling. Thesampling method uses secondary data taken from financial reports and annualreports. Data were analyzed using IBM SPSS 25. The results showed thatpressure has a positive effect on financial distress, opportunity has a positiveeffect on financial distress, good corporate governance has a negative effect onfinancial distress, good corporate governance weakens the negative influence ofpressure on financial distress, good corporate governance weakens the influencenegative opportunity to financial distress, while rasionalization andrationalization moderated by good corporate governance have no influence onfinancial distress..